Pemanfaatan Media Sosial Sebagai Sarana Promosi Jasa Make Up Artist Peserta Didik Di LKP Lelly Medan - Desipriani Desipriani; Suprianingsih Suprianingsih; Widya Oktaviani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Social media is a medium for socializing with each other and is done online which allows people to interact with each other without being limited by space and time. Social media erases human boundaries for socializing, space and time boundaries, with this social media it is possible for humans to communicate with each other wherever they are and at any time, no matter how far apart they are, and no matter day or night. Promotion is one of the variables in the marketing mix that is very important. Promotions are carried out by companies to market products and services. LKP Lelly Medan is a Skills and Training Institute in the field of bridal make-up for students who study for free because of a government program to learn about all things bridal make-up